2021
DOI: 10.4236/jss.2021.95034
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Industry 4.0 on Marketing Activities and Strategies of Iron and Steel Industry in Developing Countries: Case for Uganda

Abstract: The iron and steel industry is one of the main contributors to the total Gross Domestic Product (GDP) of most developing countries in Africa and is key for both domestic and global markets. The holistic approach to Industry 4.0 needs a wider look at the transition taking place in the area of marketing. The paper aims at investigating the impacts of Industry 4.0 on marketing activities and strategies of iron and steel companies in developing countries by identifying which consideration factors are relevant when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Based on their research, they found that Industry 4.0 technologies tend to incrementally improve the operational efficiency and productivity of the activity in question, rather than revolutionising it, while the minimum optimal scale of both plants and specific equipment remains unchanged. In the study, Komakech et al (2021) concentrate on examining the impacts of Industry 4.0 on the activities and strategies of metallurgical enterprises in Uganda. The results of the study show statistical evidence to explain the impact of Industry 4.0 on activities and strategies such as the effects of rapidly evolving technological capabilities, product quality, quantity and raw materials, increased supply chain and channel strategy, value addition, organizational realignment to integrate physical and digital technologies, market positioning, pipeline management, illicit business practices, skills shortages, research and innovation and other tools.…”
Section: Methodsmentioning
confidence: 99%
“…Based on their research, they found that Industry 4.0 technologies tend to incrementally improve the operational efficiency and productivity of the activity in question, rather than revolutionising it, while the minimum optimal scale of both plants and specific equipment remains unchanged. In the study, Komakech et al (2021) concentrate on examining the impacts of Industry 4.0 on the activities and strategies of metallurgical enterprises in Uganda. The results of the study show statistical evidence to explain the impact of Industry 4.0 on activities and strategies such as the effects of rapidly evolving technological capabilities, product quality, quantity and raw materials, increased supply chain and channel strategy, value addition, organizational realignment to integrate physical and digital technologies, market positioning, pipeline management, illicit business practices, skills shortages, research and innovation and other tools.…”
Section: Methodsmentioning
confidence: 99%
“…Main goal of Industry 4.0 is the production of systems that are flexible, adaptable to changes and able to respond to disruptions, affecting value chain providing new services and product-service systems, connecting machines, methods, and products (Crnjac et al, 2017;Komakech et al, 2021;Müller et al, 2018), by integrating innovative technologies (e.g. advanced control systems) combined with Information Technologies (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%